Step-by-step explanation:I cant tell what the equation for g(x) is but in order to solve set up the equation like… g(f(1)) so first solve f(1), which is 9(1) -8= 9-8 =1 and then plug that 1 into g(x) so if what you meant to put is g(x)= x+3 it would be (1) +3= 4.

## Answers ( )

Answer:Step-by-step explanation:I cant tell what the equation for g(x) is but in order to solve set up the equation like… g(f(1)) so first solve f(1), which is 9(1) -8= 9-8 =1 and then plug that 1 into g(x) so if what you meant to put is g(x)= x+3 it would be (1) +3= 4.